2000
DOI: 10.1046/j.1460-9592.2000.00510.x
|View full text |Cite
|
Sign up to set email alerts
|

Sedation failures in children undergoing MRI and CT: is temperament a factor?

Abstract: This study examined the relationship between temperament and sedation failure during magnetic resonance imaging (MRI) and computerized tomography (CT). One hundred and two children (aged 3-7 years) who underwent MRI or CT with or without sedation were studied. Demographics, sedatives administered, efficacy of sedation, and adverse events were recorded. Parents completed the Behavioural Style Questionnaire for 3-7 years olds during their wait. Eight children underwent MRI successfully without sedation, 83 were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
25
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 9 publications
1
25
1
Order By: Relevance
“…The children's temperament was evaluated during this initial assessment to help predict the feasibility of cooperation. This was based on the MRI nurses' experiences using CAM and a study reported by VoepelLewis, Malviya, Prochaska, & Tait (2000) who described temperament and coping strategies. Teaching the child and family how to use coping strategies along with the use of diversion activities were used as valuable tools in achieving the stillness required for a quality study (Huth, Kuiken, & Broome, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The children's temperament was evaluated during this initial assessment to help predict the feasibility of cooperation. This was based on the MRI nurses' experiences using CAM and a study reported by VoepelLewis, Malviya, Prochaska, & Tait (2000) who described temperament and coping strategies. Teaching the child and family how to use coping strategies along with the use of diversion activities were used as valuable tools in achieving the stillness required for a quality study (Huth, Kuiken, & Broome, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In 102 patients under seven years just eight patients with less activity and more patience passed MRI without the need for anesthesia 10 . In case of seriously ill or psychiatric children the use of sedation or GA is more comfortable for patients and their parents.…”
Section: Discussionmentioning
confidence: 99%
“…Children frequently require sedation in order to be cooperative and immobile for imaging modalities in radiology units, namely the magnetic resonance imaging (MRI) and computerized tomography (CT) procedures [1][2][3][4][5][6] . Moreover, imaging procedures that are not applied under adequate sedation necessitates repetition of the procedure, resulting in a significant loss of revenue to the institution, lost work time and, perhaps most importantly, delayed diagnosis.…”
Section: Introductionmentioning
confidence: 99%